ANALISIS PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING (Survei pada Tenaga Kependidikan Universitas Slamet Riyadi Surakarta) - Rahayu Triastity, Unggul Adi Purnama, Alwi Suddin & (Universitas Slamet Riyadi, 2017)
The purpose of this study is to know and analyze the significance of theinfluence of work environment, motivation, job satisfaction on theperformance of education personnel Slamet Riyadi University Surakarta,moderated by job satisfaction. The population in this study is all the staffs atSlamet Riyadi University Surakarta, amounting to 137 people. Determinationof sample using proportional random sampling, each part / unit is taken 60%from total population and then each member is chosen randomly with theamount of sample of research as much as 82 people of education. Methodsof data collection using questionnaires that have been tested for validity andreliability. The conclusion of this study is that the work environment has nosignificant effect on the performance of education personnel; work motivationhas a significant effect on the performance of education personnel; jobsatisfaction has no significant effect on the performance of educationpersonnel; job satisfaction moderate the influence of the work environmenton the performance of educational personnel; job satisfaction does notmoderate the effect of work motivation on the performance of educationpersonnel.Keywords: work environment, motivation, job satisfaction performance